(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The article deals a new electrochemical way of making long-lived, hanging silver nanoparticles and silver powders. There are no chemical stabilizing substances in the method. The morphology of the obtained silver nanoparticles was studied by means of electron transmission microscopy, electron microscopy scanner, atomic microscopy and dynamic light dispersal measurement. The creation of silver crystalline structures consisting of agglomerating silver nanoparticles on cathode surface during the electrochemical procedure was shown. Silver nanoparticles have diffuse reflective spectroscopy characterized their optical properties. From the diffuse reflection using Kubelka – Munk formula, the optical band gap energy was determined for the electrodeposited AGNPs. The crystalline character of silver nanoparticles confirmed the growth of nano silver crystals in X-ray (XRD) studies. The XRD design showed that the electrodeposited Ag NPs had a dendrite dominance in the cubic geometry. Debye–Scherrer equation was considered for the average particle size and peak expansion, while Williamson–Hall method was used to study the peak expansion strain. A high-resolution microscope of scan of electrons characterized the surface morphology of the Ag NP and results showed a high degree of particle aggregation. The antifungal activity of Ag NPs was assessed and demonstrated an unprecedented level of antibacterial activity in combination with streptomycin against multi-drug resistant strains like Staphylococcus aureus, Bacillus subtilis, Klebsiella Pnumonia and Escherichia coli.